2021
DOI: 10.1007/s11270-021-05256-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ecotoxicity of Exposure to Sugarcane Ashes on the Behaviour of Predator and Prey Fish Species

Abstract: the effects of sublethal SCA concentration on aquatic organisms. In this study, we evaluated the behaviour of a piscivorous (Hoplerythrinus unitaeniatus) and an invertivorous (Moenkhausia forestii) fish species, after a short-term (24 h) exposure to a sublethal concentration of SCA (0.8 g L −1 ). We hypothesized that the outcomes of predator-prey interaction would change when the players are subjected to sublethal SCA concentration. Our findings revealed that neither the behaviours of predator and prey fish sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(82 reference statements)
0
0
0
1
Order By: Relevance
“…stephensi (Liston) larvae compared with C. idella, Cyprinus carpio L., and O. niloticus (Ghosh et al, 2005). Earlier studies demonstrated that the predation rates of C. gariepinus and other indigenous and exotic larvivorous fi sh species were greatly associated with diff erent biological traits such as the biotype, size, developmental stages and sex of the larvivorous fi sh, and the genera, developmental stages and population density of mosquito prey (Seng et al, 2008;Chala et al, 2016;Mohamed et al, 2021), or the presence of diff erent chemical and physical stressors such as pesticides, light, and salinity in aquatic habitats (Kerby et al, 2012;Yofukuji et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…stephensi (Liston) larvae compared with C. idella, Cyprinus carpio L., and O. niloticus (Ghosh et al, 2005). Earlier studies demonstrated that the predation rates of C. gariepinus and other indigenous and exotic larvivorous fi sh species were greatly associated with diff erent biological traits such as the biotype, size, developmental stages and sex of the larvivorous fi sh, and the genera, developmental stages and population density of mosquito prey (Seng et al, 2008;Chala et al, 2016;Mohamed et al, 2021), or the presence of diff erent chemical and physical stressors such as pesticides, light, and salinity in aquatic habitats (Kerby et al, 2012;Yofukuji et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…to reduce the activity and change swimming speed behavior (rest and slow swim) that may decrease the attack capability rate on mosquito larvae. The presence of chemical contaminants such as heavy metals and pesticides in aquatic habitats may aff ect the survival and predatory ability of predatory fi sh by decreasing the predation rates, altering their swimming ability or reducing their vigor (Kerby et al, 2012;Monde et al, 2016;Yofukuji et al, 2021). Changes in ecological functions of mobility and predation may be due to the inhibitory eff ect of the toxic compounds on fi sh's acetylcholinesterase (Banaee, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas recentes têm demonstrado que as EEIs podem ser mais resistentes à contaminação da água por cinzas. Dessa forma, a chegada desse contaminante à água facilita o estabelecimento de tais espécies como resultado da perda de biodiversidade nativa (Gonino et al 2019, Yofukuji et al 2021.…”
Section: Efeitos Múltiplos Aditivos Ou De Interação Entre Os Vetores ...unclassified
“…Mechanized sugarcane harvesting brought several environmental benefits, reducing the need for labor and fires [1] and increasing agricultural performance [2]. However, mechanized harvesting also generates problems, such as increased raw impurities, field losses [3], lower cut quality [4][5][6][7] and ratoons with damage [8], resulting in fragmented stumps [9].…”
Section: Introductionmentioning
confidence: 99%